2006
DOI: 10.1143/jjap.45.8340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ion Energy Control on Production of Nitrogen–C60 Compounds by Ion Implantation

Abstract: Nitrogen–C60 compounds such as azafullerene (C59N) and nitrogen-atom-encapsulated fullerene (N@C60) are produced by implanting nitrogen ions into C60 thin films on a substrate immersed in an electron cyclotron resonance plasma under a mirror magnetic field. Each compound is found to be synthesized, depending on the ion energy provided by the potential difference between the substrate and the plasma. The optimum energy for C59N synthesis is approximately 40–50 eV, and the amount of C59N decreases in an ion ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…3 is due to the hyperfine interaction with 14 N nucleus (I = 1) and also for the electron spin of S = 3/2 [6] as discussed in the preceding section. By following previous reports [12,16], we have calculated the concentration of N@C 60 by comparing both of the integrated shaded areas of tempol and sample ( Fig. 3) with each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 is due to the hyperfine interaction with 14 N nucleus (I = 1) and also for the electron spin of S = 3/2 [6] as discussed in the preceding section. By following previous reports [12,16], we have calculated the concentration of N@C 60 by comparing both of the integrated shaded areas of tempol and sample ( Fig. 3) with each other.…”
Section: Resultsmentioning
confidence: 99%
“…N@C 60 has been synthesized by ion implantation [5], glow discharge [6,10], and radio frequency discharge [11] methods so far, and it had been reported that the irradiation of nitrogen atom ions to C 60 is necessary for the efficient synthesis of N@C 60 . However, the purity which is defined as a ratio between concentration of N@C 60 and C 60 is very low (N@C 60 /C 60 = 10 −3 % to 10 −2 %) at present [12,13]. Although the purity can be improved by high performance liquid chromatography (HPLC) [14].…”
Section: Introductionmentioning
confidence: 99%
“…The azafullerene C 59 N was synthesized by a nitrogen plasma irradiation method [8]. A plasma was produced by applying an RF power with a frequency of 13.56 MHz, and nitrogen ions in the plasma were generated and accelerated toward a substrate by a sheath electric field in front of the deposited C 60 fullerene.…”
Section: Methodsmentioning
confidence: 99%
“…An energy of approximately 100 V is favorable for producing specific materials such as diamond and fullerenes encapsulating a particle. 1,2 However, the components of low-energy ion beams diverge soon after their extraction by a grounded electrode owing to the self-electric field of ions. Therefore, technologies to suppress the beam divergence are required.…”
Section: Introductionmentioning
confidence: 99%